Gestational diabetes mellitus and adverse pregnancy outcomes increased on pandemic lockdown: a retrospective analysis - Chen, Niankun; Shi, Shaole; Zhao, Shanshan; Shen, Lixia; Kong, Lingyi; Liang, Zanxiong; Cai, Shiqin; Chen, Haitian; Wang, Dongyu; Wang, Zilian (The journal of maternal-fetal & neonatal medicine, 2025)
Adverse social contexts, such as lockdowns and disasters during pregnancy, can significantly impact maternal and neonatal outcomes. However, the specific effects on different populations remain unclear. This study aimed to investigate the variations in pregnancy outcomes resulting from the pandemic lockdown and to identify distinct populations in need of targeted intervention. Women who delivered at our institution spanning from 2017 to 2019 (pre-pandemic) and from 2020 to 2022 (during the pandemic lockdown) were included in this study. A comparison was conducted on maternal and neonatal outcomes across a total of 19,382 singleton pregnancies, with a specific focus on those affected by gestational diabetes mellitus (GDM). As a total of 19,382 singleton pregnant women were included, this study found a significant increase in the incidence rates of GDM with an odds ratio of 1.194 (95%CI: 1.109-1.286, < .001). Additionally, following the pandemic lockdown, there was an increase in rates of premature birth, premature rupture of membranes, and intrahepatic cholestasis of pregnancy. Further analysis of the GDM cohort revealed a notable rise in the risk of Group B Streptococcus infection and neonatal small for gestational age (SGA). Specifically, GDM patients with a body mass index (BMI) less than 18.5 kg/m exhibited an increased risk of fetal growth restriction and SGA. The pandemic lockdown adversely affected pregnancy outcomes. Therefore, targeted screening and clinical management for specific populations should be prioritized.